Hush Now Baby: Mothers’ and Fathers’ Strategies for Soothing Their Infants and Associated Parenting Outcomes - Dayton, Carolyn Joy (J Pediatr Health Care, 2014)
OBJECTIVES: The purpose of this study was to examine the types of soothing behaviors used by mothers and fathers of infants, differences in use trajectories over time, and associated parenting outcomes. METHODS: Longitudinal study of 241 families expecting their second child. Data were collected at 1, 4 and 8 postnatal months and included measures of parental soothing techniques, involvement in soothing, distress in response to infant crying, and parenting self-efficacy. RESULTS: Average number of soothing techniques used was 7.7 for mothers and 5.9 for fathers. Soothing frequency decreased over time and change patterns of soothing differed over time by gender. In couples who shared responsibility for soothing fathers felt more efficacious in parenting and mothers were less upset by infant crying. DISCUSSION: Clinicians are encouraged to support fathers’ engagement in infant soothing, to facilitate the development of fathers’ parenting confidence, and to promote fathers’ involvement in children’s health and healthcare.